Mortality and risk factors associated with pulmonary embolism in coronavirus disease 2019 patients: a systematic review and meta-analysis - Carlos Andrés Gómez; Cheuk-Kwan Sun; I-Ting Tsai; Yang-Pei Chang; Ming-Chung Lin; I-Yin Hung; Ying-Jen Chang; Li-Kai Wang; Yao-Tsung Lin; Kuo-Chuan Hung (Scientific Reports, 2021)
Abstract To determine, in patients with coronavirus disease 2019 (COVID-19) infection, the associations of pulmonary embolism (PE) with mortality and risk factors for PE as well as the therapeutic benefit of anticoagulant prophylaxis. Embase, PubMed, Cochrane controlled trials register, and Web of Science databases were searched from inception to October 10, 2020. We included all published trials on PE in patients diagnosed with COVID-19 with eligibility of the trials assessed following the PRISMA guidelines. Sixteen clinical trials with 5826 patients were eligible. There were significant associations of PE with the male gender [odd ratio (OR) = 1.59, 95% CI 1.28–1.97], mechanical ventilation (OR = 3.71, 95% CI 2.57–5.36), intensive care unit admission (OR = 2.99, 95% CI 2.11–4.23), circulating D-dimer [mean difference (MD) = 5.04 µg/mL, 95% CI 3.67–6.42) and CRP (MD = 1.97 mg/dL, 95% CI 0.58– 3.35) concentrations without significant correlation between PE and mortality (OR = 1.31, 95% CI 0.82–2.08) as well as other parameters or comorbidities. After omitting one trial with strict patient selection criteria for anticoagulant prophylaxis, significant prophylactic benefit was noted (OR = 0.31, 95% CI 0.1–0.91). Our findings identified the risk factors associated with PE in COVID-19 patients and supported the therapeutic benefit of anticoagulant prophylaxis against PE in this patient population.